1980
DOI: 10.1295/polymj.12.521
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Process and Dissolved State of Cellulose in Dimethylformamide–Chloral–Pyridine System

Abstract: The dissolution process and dissolved state of cellulose into a dimethylformamide-chloral-pyridine (D-C-P) system were studied by optical microscopy, nuclear magnetic resonance (NMR), polarimetry, infrared (IR) spectroscopy, and X-ray diffraction method. Natural cellulose with crystal form I dissolves rapidly at room temperature, via hemiacetaltype reaction with chloral, in which pyridine acts as a reaction accelerator. Cellulose exists as cellulose trichlorate in the mixture. When the pretreatment period of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…3 ) . Table I1 (column [11][12][13][14] shows that (1) the crystallinity x, of the new fibers is relatively high ranging 0.65-0.67, compared with those (ca. 0.6) of the commercial regenerated Table 11.…”
Section: Sem Micrographs Of the Lyophilized Fiber Of As-spun Fiber F-mentioning
confidence: 99%
“…3 ) . Table I1 (column [11][12][13][14] shows that (1) the crystallinity x, of the new fibers is relatively high ranging 0.65-0.67, compared with those (ca. 0.6) of the commercial regenerated Table 11.…”
Section: Sem Micrographs Of the Lyophilized Fiber Of As-spun Fiber F-mentioning
confidence: 99%
“…Applying the low-power selective spin decoupling method to almost completely substituted CA ({F)>=2.92), Kowsaka et al 12 assigned, from the lower magnetic field, the carbonyl carbon peaks to the acetyl groups at C6 , C 3 , and C2 positions and simultaneously demonstrated that there are not only 3 but also many peaks in the carbonyl carbon region of 13 C NMR spectra of partially substituted CA ( {F)> = 2.46 and 0.68), insisting that these peaks correspond to 12 carbonyl carbon peaks, originating from magnetically different all ( = 12) -OR groups existing in 8 pyranose rings as shown in Figure 3. In order to evaluate {fk)> for not-fully substituted CA with good accuracy, the reliable assignment of the abovementioned 12 peaks is very prerequisite because rough classification of these peaks into three parts (carbonyl at C 2 , C 3 , and C 6 ) made by Kamide 13 and Kamide and his collaborators 5 came to the same conclusion that CA samples with the same {F)>, prepared under different conditions, had different degrees of water solubility, and discussed the relations between {fk)> by NMR method and the water solubility for CA: CA having {f 2 )> {f 3 )> {f 6 )> (i.e., CA with uniformly distributed acetyl groups) dissolves almost completely in water at room temperature in the range of {F)> from 0.6 to 1.0. In contrast to this, CA having {f 6 )> {f 2 )> + {f 3 )> (i.e., CA with acetyl groups highly selectively located at C 6 position) is little better than insoluble in water over the entire {F)> range.…”
mentioning
confidence: 93%
“…1 -5 Thus, the total degree of substitution was also expressed by iF)). In addition, Kamide et al 6 showed by thin-layer chromatography (TLC) that CA sample consists of molecules with different average total degrees of substitution <F) [here, F is the degree of substitution of a given glucopyranose unit and <F) is obtained by averaging F over all glucopyranose units constituting a single molecule] and evaluated the distribution of <F), denoted as g( <F)) (see Figure 2). However, when we see the possible substituted glucopyranose units of cellulose derivative, there are 8 kinds of unsubstituted and partially or fully substituted glucopyranose units as shown in Figure 3: single trisubstituted, three disubstituted, three monosubstituted and one unsubstituted glucopyranose units.…”
mentioning
confidence: 99%
See 2 more Smart Citations